Martínez y Mallarmé: El libro total en la nueva novela - Urbano, Karolina (2019)
From the inmense intertextual variety presented on Juan Luis Martinez’s La nueva novela, this article analyzes Mallarmé’s poetic presence and the way itinfluences the general fonction of this controversial book, being bonded to the idea of total book defended by the french poet. In La Nueva Novela an idea oftotality is set up, being able to enhance an ambixious and impossible relationship between the conception of total Book. Also, Martinez’s knowledge is shown along with the ideas given by Mallarmé: poetic language independence and the end of representation, and the way how the chilean poet presents these elements inside the formal structure of his experimental book.